2013
DOI: 10.1038/jidsymp.2013.7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hair Follicle Immune Privilege Collapse in Alopecia Areata: Status and Perspectives

Abstract: Alopecia areata (AA) may represent a CD8+T cell-mediated, organ-specific autoimmune disease in which as yet elusive autoantigens are recognized, once they become exposed by ectopic major histocompatibility complex class I expression by anagen hair follicles (HFs) that have lost their relative immune privilege (IP). On this basis, AA research is chiefly challenged with identifying the autoreactive CD8+T cells and their cognate autoantigens as well as key inducers of HF-IP collapse and "HF-IP guardians" that pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 24 publications
3
65
0
3
Order By: Relevance
“…Under normal physiological conditions a local immune-inhibitory signaling milieu in and around the hair follicle is generated that suppresses the surface molecules required for presenting autoantigens to NK cells, including CD8 + T lymphocytes. Although the function (or functions) of this hair follicle immune privilege are not proven 7174 , it is believed that several autoantigens that are related with pigment production in melanocytes are immunogenic and, under the right circumstances, can result in loss of immune privilege 75 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…Under normal physiological conditions a local immune-inhibitory signaling milieu in and around the hair follicle is generated that suppresses the surface molecules required for presenting autoantigens to NK cells, including CD8 + T lymphocytes. Although the function (or functions) of this hair follicle immune privilege are not proven 7174 , it is believed that several autoantigens that are related with pigment production in melanocytes are immunogenic and, under the right circumstances, can result in loss of immune privilege 75 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…19 Several hair loss disorders outlined below have been associated with MCs. [20][21][22][23][24][25][26][27][28][29] Currently, these findings are of scientific value without direct diagnostic application to practice.…”
Section: Giemsa and Toluidine Blue For Mast Cellsmentioning
confidence: 95%
“…23 Substance P and interferon gamma are implicated as the most important inducers of the collapse of the immune privilege of the hair follicle in AA. 24 Recently, Bertolini et al 22 showed that not only are MCs increased in lesional AA biopsies from human and mouse skin but they also interact with the CD8 + T cells, thus promoting their pathogenic responses against hair follicles. the vertex in men with AGA when compared with the vertex of men with normal hair density.…”
Section: Alopecia Areatamentioning
confidence: 98%
“…Hair follicles with their characteristic low-surface major histocompatibility complex (MHC) are classified as an immune privilege site, a title mainly attributed to several vital organs including the brain, testes, and cornea [20]. EPD may have an association with other autoimmune diseases [1,21].…”
Section: Discussionmentioning
confidence: 99%